Peculiar Features of Comedy Genre in Uzbek Literature (On the Example of Utkir Khashimov`S Works) - Lola Jalilovna Jalilova; Rajabov Akhtam Uktamovich (Researchparks Publishing, 2021)
This article deals with the study of peculiar features of comedy genre in Uzbek literature. Satirical works of Utkir Khashimov are analyzed. The skilful implementation of folklore in writer`s works is a reason of their interest for audience, as it is a reflection of the national culture. We can also observe that Utkir Khashimov uses in his works one of the common genres of oral folk art - the genre of fairy tales. The desire to struggle against the vices of life naturally leads U. Khashimov to satire. Elements of satire are found almost in every work of the writer. At the same time, the writer fruitfully uses, along with various means, the spiritual confessions of the heroes, their inner monologues, that is the manifestation of a deep analysis of the moral world of man, his psychology.